Chemical compositions of amphiboles and their references to formation conditions of granitoids from Nam Rom and Song Ma massifs, Northwest Vietnam - Can, Pham Ngoc; Anh, Tran Tuan; Hoa, Tran Trong; Ly, Vu Hoang; Lien, Pham Thi Phuong; Huong, Ngo Thi (Vietnam Journal of Earth Sciences, 2020)
In this paper, the mineralogical and geochemical characteristics of amphiboles and plagioclases of granitoids from the Nam Rom and Song Ma massifs have been investigated to understand their formation conditions. The Nam Rom amphibole and plagioclase are subhedral to euhedral fine- to medium-grained crystals. Whereas, the Song Ma amphibole and plagioclase are anhedral to subhedral fine-grained crystals. Geochemical compositions of amphiboles suggest that Nam Rom and Song Ma amphiboles are edenite and ferro-edenite, respectively. Nam Rom edenite has higher contents of basic constituents (Mg and Ca) and lower contents of felsic constituents (Na and K) compared with the Song Ma ferro-edenite. On the other hand, Si-(Na+K) and Si-Ca apfu ratios of the Nam Rom edenite and the Song Ma ferro-edenite and Al/(Na+K)-Al/(Ca+Na+K) atom per formula unit (apfu) ratios of the Nam Rom edenite and andesine and the Song Ma ferro-edenite, andesine and oligoclase are similar. Formation conditions of the Nam Rom and Song Ma granitoids were calculated using amphibole-plagioclase geobarometer. The Nam Rom granitoid was formed at 3.07-5.32 kbar (10.1-17.6 km under paleo-surface) and 750-785°C. The Song Ma granitoid was formed at 1.04-3.08 kbar (3.4-10.2 km under paleo-surface) and 715-745°C. Therefore, Nam Rom and Song Ma granitoids are thought to be crystallized from the same magma. The former was formed from the immature and more basic stage of magma; the latter was formed from the mature and more felsic stage of magma.